Enculturation of entrepreneurial values in the family of gebyok carvers in Blimbingrejo, Jepara - Alkhairunisa, Ayna Ayu; Wasino, Wasino; Rachman, Maman (Universitas Negeri Semarang, 2024)
Carving is a characteristic of Jepara Regency, one of which is gebyok carving in Blimbingrejo Village, Jepara Regency, which needs to be preserved through a process of cultural enculturation to the next generation so that the characteristics of the business in the area continue. This article explored the enculturation or inheritance of entrepreneurial values in the family of carvers and the impact of the enculturation process. The method used in this article was qualitative, with data collection through in-depth interviews, observation, and documentation. The results first, carving entrepreneurship, especially gebyok in Blimbingrejo village, took place across generations through the process of enculturation of values in three families, which used different ways in the family internalization process including the process of apprenticing children for readiness to continue this gebyok carving culture. Second, the impact of inheritance of entrepreneurial values included social and economic impacts. Social impacts included the creation of intimacy between residents and increased social relations. The economic impact brought the community to a better standard of living and opening up jobs so. This research concluded to implement the enculturation process through an internalization process that can increase the younger generation's interest in preserving the carving culture.